Trackers for Adverse Events in Child Mental Health: descriptive analysis using the global trigger tool - Sandna Larissa Freitas dos Santos; Ana Paula Soares Gondim (Brazilian Journal of Pharmaceutical Sciences, 2023)
Abstract The goal of this study is to identify the global trigger tool trackers used to place the adverse drug events presented in children that use psychotropic drugs accompanied by Child-adolescent Psychosocial Care Centers. This is a descriptive study carried out with the secondary data of 112 child care records that began in January 2017 in two Child-adolescent Psychosocial Care Centers. A median of medicine per child was 1.71 and among the most used we were to risperidone 100%, followed by valproic acid and periciazine with 16% each. A total of 42 adverse drug events were found in 36 medical records, being agitation 29.7% and agressive 16.2%, being the most frequent, and in 45.2% of infants presenting only one event. 50 were trackers detected in 83.3%, two records that identified adverse drug events. In 38.8% were found only one tracker, the most found ones were: combination of psychotropic medicines 32%, abrupt reduction of medicine dose 22% and abrupt cessation of medicine 12%. Finally, the present study showed that the global trigger tool evidenced adverse drug events by means of the detection of trackers in children and that it had to offer interventions to improve the quality of psychiatric therapy within two community services.